Portfolio optimization using a new probabilistic risk measure - Sun, Y.; Aw, Ee-Ling Grace; Teo, Kok Lay; Teo, Kok Lay; Zhou, Guanglu (American Institute of Mathematical Sciences, 2015)
In this paper, we introduce a new portfolio selection method. Our method is innovative and flexible. An explicit solution is obtained, and the selection method allows for investors with dierent degree of risk aversion. The portfolio selection problem is formulated as a bi-criteria optimization problem which maximizes the expected portfolio return and minimizes the maximum individual risk of the assets in the portfolio. The ecient frontier using our method is compared with various ecient frontiers in the literature and found to be superior to others in the mean-variance space.